Impact of human leukocyte antigen and calculated panel reactive antibody on BK viremia in kidney transplant recipients: A single‐center experience and literature review. Issue 4 (18th May 2019) - El‐Husseini, Amr; Hassan, Waleed; Yaseen, Maria; Suleiman, Belal; Saleh, Sherif; Malik, Omar; Ashqar, Hasan; Maibam, Amita; Mei, Xiaonan; Castellanos, Ana L.; Cornea, Virgilius; Gedaly, Roberto; et al.
Abstract: Background: The aim of this retrospective analysis was to investigate the effect of human leukocyte antigen (HLA) and calculated panel reactive antibody (cPRA) on BK virus activation as evidenced by BK viremia (BKV). Patients and Methods: At our institution, 649 kidney transplant patients were screened for BKV from 2009 to 2017. Patients were considered to have BKV if they had >10 000 copies/mL of BK DNA in their blood. Donor and recipient HLA and cPRA, demographic, clinical and laboratory data, as well as immunosuppressive medications were collected. Results: We identified 122 BK positive and 527 BK negative patients. Only 25% of the patients had cPRA of 20% or more, and 64% had more than three HLA‐A, ‐B, and ‐DR mismatches. In both univariate and multivariate analyses, male gender, age, and maintenance of steroid therapy significantly increased the risk of BKV ( P  = 0.005, 0.005 and <0.001, respectively). The degree of cPRA and the individual HLA allele and HLA allele matching did not significantly affect BKV. Conclusion: Neither the degree of HLA mismatching nor cPRA appears to affect BKV. Moreover, no specific HLA allele, HLA allele matching, or cPRA were associated with BKV.